Pelatihan Kepemimpinan dan Pengembangan Manajerial: Strategi Meningkatkan Kompetensi Individu dan Efektivitas Organisasi melalui Pendekatan Kualitatif - Sutarso, Al Bait Fiqri Zulfikar; Al Ghifari, Abdillah; Firdaus, Firman; Yughatama, Yoram; Veranita, Mira (CV. Kalimasada Group, 2025)
Leadership training and managerial development are essential elements in improving human resource quality and organizational effectiveness. This study aims to explore the processes and impacts of leadership training and managerial development using a descriptive qualitative approach. Data were collected through literature review, interviews with managerial practitioners, and observations of training implementation within organizational settings. The findings indicate that well-designed training significantly enhances communication skills, decision-making, team management, as well as employee satisfaction and retention. Training methods such as simulation, coaching, job rotation, and thematic training in operations, marketing, and human resources play a vital role in shaping adaptive and responsive leaders. These findings highlight the importance of continuous training programs that are relevant to organizational needs and supported by technology integration and a strong learning culture.